Phytochemical constituents and radical scavenging properties of Borago officinalis and Malva sylvestris - Mohajer, S.; Taha, R.M.; Ramli, R.; Mohajer, M. (Elsevier, 2016)
In order to find possible sources for future novel antioxidants in food and pharmaceutical formulations, phytochemical constituents and antioxidant activities of methanol extract polar and nonpolar subfractions of Borage (Borago officinalis) and Common mallow (Malva sylvestris) were determined. Identification of two alkaloids (Sanguinarine and Berberine) and water-soluble vitamins in HPLC chromatograms have been settled in comparison of the retention time and peak area with those observed for authentic standards. Antioxidant activities were evaluated by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging (FRS), ferrous ion (Fe2+) metal chelating and ferric ion (Fe3+) reducing power (FRAP). Hydrogen peroxide was also disposed by catalases (CAT) and peroxidase (POX) activities. The total content of tannins, flavonoids, phenolic acids and polyphenols have been expressed as tannic acid (TA), (+)-catechin (CE), gallic acid (GAE) and pyrogallol (PyE), respectively. In addition, M. sylvestris exhibited stronger ferrous ion chelating and peroxidase activity compared with B. officinalis. A relatively high concentration of vitamin C was also recorded in M. sylvestris with 38.01 mg/100 g DW. The findings suggest that the pigments derived from natural plants may have direct relation with biological activities and exhibit different properties. Also all other soluble compounds present in the extracts, their possible antioxidant activity and interactions need to be elucidated in order to fully explain the final antioxidant capacity of the extracts.